Structural and functional responses of macrobenthic communities to climate variability: a comparison between distinct climate scenarios - Abreu, Anthony Martins de (2013)
Dissertação de mestrado em Ecologia, apresentada ao Departamento Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.